Entrepreneurial universities : exploring the academic and innovative dimensions of entrepreneurship in higher education - Peris-Ortiz, Marta; Gómez, Jaime Alonso; Merigó-Lindahl, José; Rueda-Armengot, Carlos (Springer, 2017)
"This book analyses the importance of the entrepreneurial university, specifically in relation to the creation of entrepreneurial ideas and attitudes in students and entrepreneurial initiatives in academic institutions. The aim of the editors and contributing authors is to provide the reader with a set of experiences illustrating the advantages of communicating and encouraging entrepreneurship among students, thereby highlighting the 'third mission' of the university: the need to adopt entrepreneurial strategy without disrupting the equality of teaching and research. Featuring initiatives from institutions around the world, the authors argue that the increasing importance of knowledge in the technical and social dimensions of today's world provides greater relevance to the entrepreneurial university. In this context, universities transcend their traditional focus on teaching and basic research to carry out technology transfers, marketing ideas, and patent registrations, and incorporate spin-off companies that contribute to industrial innovations, economic growth, and job creation. In the teaching dimension, the entrepreneurial university represents a focus on programs which train students in the applications and most advanced practices in knowledge-driven fields. The book addresses such questions as: Can marketing ideas deteriorate the quality of research in the long term? What importance does the cultural framework have for an entrepreneurial education? What circumstances and programs facilitate spin-offs in universities What are the key features of entrepreneurial universities? In reference to entrepreneurship education in its broadest sense, then, it corresponds to the framework of ideas and general features on which entrepreneurship is founded: in-depth knowledge of the projects or ventures which they wish to carry out, capacity to perceive the relevant characteristics of the environment, and the leadership and goal setting skills to achieve success"--Provided by publisher.
Keywords: Entrepreneurship -- Study and teaching (Higher); elektronické knihy; electronic books